Case Report: Congenital neurosyphilis presenting as post-hemorrhagic hydrocephalus in a preterm infant and a review of literature - De Rose, Domenico Umberto; Martini, Ludovica; Ronchetti, Maria Paola; Longo, Daniela; Guarnera, Alessia; Santisi, Alessandra; Carrara, Stefania; De Benedictis, Alessandro; Cortazzo, Venere; Perno, Carlo Federico; Bonanno, Elvira; Dotta, Andrea; et al. (Frontiers in Pediatrics, 2025)
BackgroundCongenital syphilis (CS) remains a global public health concern, with rising incidence even in high-income countries. In Italy, a higher risk has been reported among primigravidae and younger mothers with late or missed prenatal screening. While neurological involvement in CS is well known, it is rarely reported in preterm infants, where it may be severe and atypical.Case presentationA male preterm infant, delivered at 32 weeks via emergency cesarean due to abnormal fetal monitoring and breech position, was admitted to our NICU with intraventricular hemorrhage, midline shift, and hydrocephalus, requiring neurosurgery. He later developed a metaphyseal bone lesion; Staphylococcus aureus was found in blood cultures. Despite antibiotics, persistent thrombocytopenia and infectious symptoms led to further testing, revealing congenital syphilis with neurological involvement and osteomyelitis and osteochondritis of the distal ulna and radio from an undetected maternal treponemal infection during pregnancy. Penicillin therapy produced slow recovery, but the newborn developed epilepsy and spastic tetraplegia by 24 months. Genetic and metabolic tests were negative. Literature review rarely shows similar CS cases, especially in preterm infants.ConclusionThis case highlights the relevance of universal maternal syphilis screening and early neonatal evaluation. Maternal Treponema pallidum infection during pregnancy can result in preterm birth and may be associated with neurological complications, such as hemorrhages, seizures, and motor impairment, which can require multidisciplinary management and long-term follow-up.